The co-phasing detection method for sparse optical synthetic aperture systems - 刘政 王胜千 饶长辉 (Chinese physics B, 2012)
Co-phasing between different sub-apertures is important for sparse optical synthetic aperture telescope systems to achieve high-resolution imaging. For co-phasing detection in such a system, a new aspect of the system＇s far-field interferometry is analysed and used to construct a novel method to detect piston errors. An optical setup is built to demonstrate the efficacy of this method. Experimental results show that the relative differences between measurements by this method and the criterion are less than 4%, and their residual detecting errors are about 0.01 A for different piston errors, which makes the use of co-phasing detection within such a system promising.